FAKTOR DETERMINAN RISIKO ANEMIA PADA WANITA USIA SUBUR (WUS) DI DUA PROPINSI DI INDONESIA - Sri Prihatini (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2008)
Determinant Factors of Anemic On Women of Reproductive Age (WORA) In Two Provinces In Indonesia.Background: Anemic is still one of main nutrition problems in Indonesia. About 27% of woman of reproductive age and 48% of under fives are anemic problem. One of the caused of high prevalence anemic in Indonesia was low level of iron consumption on daily meals. In addition there could be other factors that influence on the occurance of anemic.Objectives: To study the determinant factors that associated with anemic on woman of reproductive age.Methods: The design of the study is cross-sectional. The study was conducted in four regencies selected purposively in Bali and Banten provinces. The samples were 576 women of reproductive age (WORA) aged 15-40 years old. Data collected are food consumption by using Semi Quantitative Questioner Food Frequency (FFQ), socio economics, parity, family planning, food supplement, anthropometric and Haemoglobine level. Bivariate analysis and logistic regression were used to determine relation factors associated with anemia.Results: The result of bivariate analysis showed significant association between anemic and frequency food consumption <=2 times for a week for meat (OR=2.819; Cl=1.968-4.038), fresh fish (OR=1.641 ; Cl=1.180-2.284), vegetables (OR=1.930; Cl=1.360-2.739) and fruits (OR= 1.527; Cl=1.161-2.437). Other significant factors associated with anemic were, parity >= 3 (OR=2.316, Cl=1.438-3.413), family planning (OR=0.658, Cl=0.460-0.940) and consuming supplement (OR=0.440, Cl=0.243-0.803). Furthermore, logistic regression analysis showed that meat consumption more than twice for a week associated with reduction of the risk of anemic by 47% and parity three times or more, increased risk of anemic by 2.85 times compared with women with parity less than three times.Conclusions: The consumption of meat <= 2 times for a week and parity >= 3 times were the determinant factors for anemic in women of reproductive age (WORA).Keywords: anemic, women of reproductive age, determinant factors.